Alcohol consumption and internalising disorders in young adults of ALSPAC: a population-based study. Issue 12 (6th July 2020) - Fernandes, Gwen Sascha; Lewis, Gemma; Hammerton, Gemma; Abeysekera, Kushala; Mahedy, Liam; Edwards, Alexis; Lewis, Glyn; Hickman, Matthew; Heron, Jonathan
Abstract : Introduction: Depression and harmful alcohol consumption contribute significantly to the global health burden, but in young adults, this relationship is under-researched and conflicted. The aim of this study was to determine the sex-based prevalence and the association between internalising disorders such as depression and alcohol use disorders. Method: Using the Avon Longitudinal Study of Parents and Children, we assessed the sex-specific prevalence of International Classification of Diseases, Tenth Revision diagnosed generalised anxiety disorder (GAD), depression and fear-based anxieties (FBA) at 24 years (n=3572). We examined the association between internalising disorders and alcohol consumption using the Alcohol Use Disorder Identification Test for Consumption 5+ threshold and Diagnostic and Statistical Manual on Mental Disorders defined criteria for alcohol dependence. Results: Women reported more GAD (11.6% vs 6.5%), depression (13.4% vs 6.9%) and FBA (1.3% vs 0.5%) than men (p<0.001). Harmful drinking, after adjustment for sex and socioeconomic status, was associated with a higher prevalence of depression (OR 1.8, 95% CI 1.3 to 2.4, p<0.001), anxiety (OR 1.4, 95% CI 1.0 to 2.0, p<0.001) and FBA (OR 2.4, 95% CI 1.04 to 5.56, p=0.009) compared with lower-risk drinkers. In contrast, hazardous drinking was associated with a lower prevalence of GAD (OR 0.69, 95% CI 0.54 to 0.88) and depression (OR 0.68, 95% CI 0.54 to 0.86) compared with lower-risk drinkers. Conclusions: Young adults in the UK who drink harmfully are more likely to have depression and other internalising disorders. Further research should test whether there is a J-shaped relationship between alcohol consumption and mental health in young people and whether this varies across the life course.